2023
DOI: 10.1128/mbio.03116-22
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Chronic Infection Selects for Effective Colonizers of Metaplastic Glands

Abstract: Chronic infection with Helicobacter pylori is the primary risk factor for developing stomach cancer. As disease progresses H. pylori must adapt to a changing host tissue environment that includes induction of new cell fates in the cells that line the stomach.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…According to our findings, the vacA s1i1d1m1c1n1 type is the most prevalent in H. pylori -Mon ( Table S5 ). SabB is a putative adhesin that arose via a gene fusion involving the sialic acid-binding adhesin (SabA) gene [ 50 ]. However, very little is known about the role of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our findings, the vacA s1i1d1m1c1n1 type is the most prevalent in H. pylori -Mon ( Table S5 ). SabB is a putative adhesin that arose via a gene fusion involving the sialic acid-binding adhesin (SabA) gene [ 50 ]. However, very little is known about the role of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about the role of this protein. A SabB, according to the findings of one study, may have a role in the changing gastric environment during the development of gastric disease by encouraging bacterial adhesin gene variation linked with increased colonization [ 50 ]. In a meta-analysis of 18 studies, “on” oipA status was associated with higher odds of PUD and GC [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antrum contains gastrin-secreting G cells that stimulate gastric acid secretion and somatostatin-secreting D cells that inhibit gastric acid secretion ( 26 ). Previous studies have shown that H. pylori preferentially colonizes the antrum at early stages of infection, leading to antral inflammation ( 27 , 28 ). H. pylori- induced atrophic gastritis (characterized by a loss of parietal and chief cells from the corpus) can develop over the course of infection, typically beginning in the antrocorporal transitional mucosa (the junction between the antrum and the corpus) and spreading proximally along the lesser curvature of the stomach ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 The incidence of gastric cancer attributable to H. pylori infection is approximately 75%. 5 H. pylori often infects individuals during childhood and can persist in the gastric mucosa for life in the absence of eradication therapy. 6 Chronic infection with H. pylori exposes the gastric mucosa to various bacterial components such as lipopolysaccharide (LPS), outer membrane vesicles (OMVs), and toxic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the infection rate of H. pylori is remarkably high (90%) in patients with atrophic gastritis and intestinal metaplasia 4 . The incidence of gastric cancer attributable to H. pylori infection is approximately 75% 5 . H. pylori often infects individuals during childhood and can persist in the gastric mucosa for life in the absence of eradication therapy 6 …”
Section: Introductionmentioning
confidence: 99%